2014
DOI: 10.2967/jnumed.114.140913
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Simplified Methods to Measure 18F-FLT Uptake Changes in EGFR-Mutated Non–Small Cell Lung Cancer Patients Undergoing EGFR Tyrosine Kinase Inhibitor Treatment

Abstract: 3′-deoxy-3′-18 F-fluorothymidine ( 18 F-FLT) PET/CT provides a noninvasive assessment of proliferation and, as such, could be a valuable imaging biomarker in oncology. The aim of the present study was to assess the validity of simplified quantitative parameters of 18 F-FLT uptake in non-small cell lung cancer (NSCLC) patients before and after the start of treatment with a tyrosine kinase inhibitor (TKI). Methods: Ten patients with metastatic NSCLC harboring an activating epidermal growth factor receptor mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Similar observations were made in patients with non-small cell lung cancer [23] as well as in mice bearing subcutaneous human epithelial carcinoma and Lewis lung carcinoma tumors [12].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar observations were made in patients with non-small cell lung cancer [23] as well as in mice bearing subcutaneous human epithelial carcinoma and Lewis lung carcinoma tumors [12].…”
Section: Discussionsupporting
confidence: 75%
“…Since k4 was found to be of the same order of magnitude as k3 (k3/k4 = 0.9 ± 0.3), calculating K FLT was not sensible and only DV tot was considered from the obtained kinetic parameters. SUV mean and TBR mean were calculated from late static [ 18 F]FLT images (70-90 min post-injection) and can be considered as simplified models for irreversible and reversible kinetics, respectively [23]. In this study, DV tot showed a very strong correlation with both static imaging Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All 18 F-FDHT-avid tumors were delineated on an averaged image generated from the last 15 min of the dynamic 18 F-FDHT scan, using a 50% isocontour of SUV peak (sphere of 1.2-cm diameter, positioned to maximize its mean value) corrected for local background to obtain volumes of interest ( Fig. 1) (12). Time-activity curves were produced by projecting tumor volumes of interest on the dynamic 18 F-FDHT and, when applicable, 15 scans by placing a 2 · 2 voxel volume of interest centrally on the ascending aorta in 5 consecutive planes using an early frame in which the blood pool was clearly visible.…”
Section: Discussionmentioning
confidence: 99%
“…Ordered-subset expectation maximization was used for reconstruction of the images. In addition, during the dynamic 18 F-FDHT scan, 3 manual venous samples were drawn from a separate intravenous cannula at 5, 10, and 30 min after injection (12). For all samples, whole-blood and plasma activity concentrations were measured, as well as parent and metabolite fractions of 18 F-FDHT.…”
Section: Patientsmentioning
confidence: 99%